Detection Survey of Khapra Beetle in Stored Agricultural Products in Central Java - Suciati Hadi Wuryaningsih; Y. Andi Trisyono; Witjaksono Witjaksono (Universitas Gadjah Mada, 2009)
Khapra beetle, Trogoderma granarium Evert (Celeoptera: Dermestidae) entered Central Java together with importation of stored products four decades ago. A survey was conducted to detect whether the Kaphra beetle existed in Central Java after they had been fumigated during commodity arrival. If the Kaphra beetle is absent, the data could be treated as the starting point toward declaring a pest free area (PFA) of Kaphra beetle in Central Java. The survey employed the procedure established in Australia, except this survey lasted for 11 months starting from April 2008 to February 2009. Insect traps (Trécé Incorporation, Oklahoma, USA) were placed in eight sites distributed in six districts identified as high risk for Kaphra beetle. The traps were substituted following the label. The traps were checked every 2–4 weeks making the total observations varying from 18–24 times, except one site (eight times). No Kaphra beetle was observed during this detection survey. This finding strongly suggests that Kaphra beetle is not present in Central Java. Survey should be continued to collect data sufficient to declare PFA of Kaphra beetle.